2007
DOI: 10.1007/s00423-007-0208-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological profile and long-term outcome in young adults with gastric cancer: multicenter evaluation of 214 patients

Abstract: GC in young adults demonstrates only minor deviations from the general population with a similar long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 44 publications
7
40
0
7
Order By: Relevance
“…This finding is similar to other reports on young GC patients [13,16] and it may be attributable to a lack of screening endoscopy in the typically asymptomatic young population. Population screening for GC varies between countries in both methods and screening intervals.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is similar to other reports on young GC patients [13,16] and it may be attributable to a lack of screening endoscopy in the typically asymptomatic young population. Population screening for GC varies between countries in both methods and screening intervals.…”
Section: Discussionsupporting
confidence: 81%
“…However, there has been some concern about a trend toward steadily increasing GC in young patients over the past few decades and studies were conducted to define the demographic, clinicopathologic and prognostic factors of GC in young patients [10][11][12]. The incidence of GC in patients aged 40 years or younger ranges from 4.6 to 6.2 % [12][13][14]. The clinicopathological features of GC in young patients are known to be different from older patients.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds with other investigations [28]. In our study there was no significant influence in overall survival related to tumor localization.…”
Section: Discussionsupporting
confidence: 93%
“…Factors that contribute to the poor prognosis of gastric cancer in the young include delayed detection, resulting in an advanced stage at presentation, diffuse infiltration of the tumor and a poorly differentiated histology [1,4,10]. On the other hand, recent studies have indicated that prognosis in young patients is equivalent to [7,11,12] or better than that in middle-aged patients with cancers at the same stage [8,9,13,14]. Thus, the concept of gastric cancer having a poorer prognosis in relatively young patients remains controversial.…”
Section: Introductionmentioning
confidence: 98%
“…However, the results of previous studies focusing on young patients with gastric cancer have not been convincing because of the small number of patients and lack of recent data. Moreover, the definition of ''early onset'' has varied among studies (e.g., disease occurrence at less than 30, 35, 40 or 45 years of age [3,10,13,14]). In addition, few studies have compared young and middle-aged patients epidemiologically or focused specifically on the clinicopathological characteristics of younger patients.…”
Section: Introductionmentioning
confidence: 99%